2022
DOI: 10.13057/biodiv/d231120
|View full text |Cite
|
Sign up to set email alerts
|

First report of entomopathogenic fungi from South Sumatra (Indonesia): pathogenicity to egg, larvae, and adult of Culex quinquefasciatus

Abstract: Abstract. Ramayanti I, Herlinda S, Muslim A, Hasyim H. 2022. First report of entomopathogenic fungi from South Sumatra (Indonesia): pathogenicity to egg, larvae, and adult of Culex quinquefasciatus. Biodiversitas 23: 5695-5702. Mosquito control has currently used many biocontrol agents, such as entomopathogenic fungi. So, the study aimed to determine the pathogenicity of the entomopathogenic fungi from South Sumatra to the eggs, larvae, and adults of Culex quinquefasciatus. The fungal isolates used were eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
2
1
Order By: Relevance
“…albopictus larvae. The mortality rate of larvae treated with fungi in the present research was higher than in previous researches (Ramayanti et al 2022;2023) because broth fungal culture enriched with liquid compost was used in this study. The liquid compost can increase the fungal pathogenicity (Suwandi et al 2018).…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…albopictus larvae. The mortality rate of larvae treated with fungi in the present research was higher than in previous researches (Ramayanti et al 2022;2023) because broth fungal culture enriched with liquid compost was used in this study. The liquid compost can increase the fungal pathogenicity (Suwandi et al 2018).…”
Section: Discussioncontrasting
confidence: 52%
“…Previous studies indicated that entomopathogenic fungi were promising candidates for the control of immature stages and adult of Culex (Greenfield et al 2015;Ramayanti et al 2022), Aedes (Alkhaibari et al 2016;Quintero-Zapata et al 2022;Ramayanti et al 2023), and Anopheles mosquitoes (Valero-Jiménez et al 2014;Vivekanandhan et al 2022). Entomopathogenic fungi are the most commonly used for the control of Aedes mosquitoes (Greenfield et al 2015), and some species of them have been reported to be effective in killing the larvae of Ae.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, eggs exposed to B. bassiana and M. anisopliae killed eggs directly. They could continue to kill the emerging larvae, pupae, and adults of Culex quinquefasciatus Say 1823 (Ramayanti et al 2022) and Aedes aegypti Linnaeus 1762 (Ramayanti et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…During field application, the efficacy of fungus can also be increased by adding surfactants to the fungal suspension. Ramayanti et al (2022) suggested using synthetic oil surfactants in entomopathogenic fungi applications. No studies have examined the efficacy of L. lecanii in regulating the soybean pod-sucking bugs R. linearis using the addition of alkylaryl polyglycol ethers and alkyl glycerol phthalates synthetic oil.…”
Section: Surfactantmentioning
confidence: 99%